2021
DOI: 10.1111/1756-185x.14241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psoriatic arthritis on the strength, proprioception, skill, coordination, and functional condition of the hand

Abstract: Background: This study was planned to evaluate the strength, proprioception, skill, coordination, and functional condition of the hand in individuals with psoriatic arthritis and to correlate disease activity with these parameters.Methods: Fifty-six individuals (psoriatic arthritis group, n = 36; control group, n = 20)were included in the study. Evaluations were performed of disease activity with Disease Activity Score 28; grip strength with a dynamometer and pinch strength with pinch gauge dynamometers; joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Proske and Gandevia suggested that damaging forced lengthening contractions are to blame for impaired proprioception [ 39 ]. Notably, research is also emerging that impaired proprioception is part of the clinical picture of psoriatic arthritis [ 40 , 41 , 42 ], not to mention the accumulating evidence on the involvement of neurogenic mechanisms in the disease pathomechanism of psoriasis [ 43 , 44 ]. Furthermore, the existence of an underlying systemic silent pathophysiology is telling; new psoriatic lesions could evolve due to mechanical injury on previously uninvolved [ 45 ], already dysregulated skin areas [ 46 ].…”
Section: Quad-phasic Non-contact Injury Modelmentioning
confidence: 99%
“…Proske and Gandevia suggested that damaging forced lengthening contractions are to blame for impaired proprioception [ 39 ]. Notably, research is also emerging that impaired proprioception is part of the clinical picture of psoriatic arthritis [ 40 , 41 , 42 ], not to mention the accumulating evidence on the involvement of neurogenic mechanisms in the disease pathomechanism of psoriasis [ 43 , 44 ]. Furthermore, the existence of an underlying systemic silent pathophysiology is telling; new psoriatic lesions could evolve due to mechanical injury on previously uninvolved [ 45 ], already dysregulated skin areas [ 46 ].…”
Section: Quad-phasic Non-contact Injury Modelmentioning
confidence: 99%
“… 13–15 As these symptoms may impact hand grip and function, it is important to evaluate safe and effective self-injection of bimekizumab in patients with active PsA. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] As these symptoms may impact hand grip and function, it is important to evaluate safe and effective self-injection of bimekizumab in patients with active PsA. 16,17 Here, the results from DV0004 (NCT04109976), a sub-study of the Phase 3 study BE VITAL (NCT04009499) are presented. The study evaluated safe and effective self-injection of bimekizumab by patients with PsA using the 1 mL bimekizumab SSy or the 1mL AI.…”
Section: Introductionmentioning
confidence: 99%